Analisa Faktor-Faktor yang Berhubungan dengan Perilaku Makan Mahasiswa Tingkat Akhir Fakultas Kedokteran Universitas Pembangunan Nasional “Veteran” Jakarta Tahun 2020 - Maya Kartika Hadiyuni; Luh Eka Purwani; Nunuk Nugrohowati (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: Eating behavior is the way a person thinks, is knowledgeable, and has views about food which is expressed in the form of eating. Deviant eating behaviors can be caused by a variety of factors, one of which is the stress condition commonly experienced by final-level students.. Objective: This study aims to determine the factors associated with the eating behavior of final-level students. Methods: The study used cross-sectional analytical studies on 49 respondents with stratified random sampling techniques. Data was collected using a questionnaire conducted online via google-form. The questionnaire that has been made by previous researchers has been tested for validity and reliability.  Results: The results showed that the majority of respondents had female gender (73.5%), good eating behavior (69.4%), positive body image perception (61.2%), moderate stress level (51%), and positive emotional eating (51%). Based on bivariate analysis there was a relationship between perception of body image and eating behavior (p = 0.029). Conclusion: Therefore, students are advised to build good confidence in order to create a positive perception of body image, so that they can have good eating behaviors with high levels of productivity. Keywords: eating behavior; gender; body image perception; stress; emotional eating; final year student.